2015
DOI: 10.1097/nne.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Using Gagne’s 9 Events of Instruction to Enhance Student Performance and Course Evaluations in Undergraduate Nursing Course

Abstract: Teaching large numbers of students can be a challenge for both teachers and students. Implementing new teaching strategies may be 1 way to address the problem. This paper presents the impact of using Gagne's 9 events of instruction on student learning and course evaluations over a 3-semester period. Student evaluation ratings indicated enhanced teacher mastery, effectiveness, and enthusiasm. Overall student final grades increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…The reading habits of students improved significantly following their participation in the activity due to the increase in depth and content of the questions posed by the students during discussion. This observation is in line with the findings of Miner et al [ 35 ].…”
Section: Resultssupporting
confidence: 94%
“…The reading habits of students improved significantly following their participation in the activity due to the increase in depth and content of the questions posed by the students during discussion. This observation is in line with the findings of Miner et al [ 35 ].…”
Section: Resultssupporting
confidence: 94%
“…In many studies in which the teaching activities model by Gagne was examined in comparative groups, the results that the success in the experimental groups for whom the courses were designed and applied by using the teaching activities model by Gagne was higher than the success in the control groups (Karabagshiew, 2003;Menzi, 2012;Miner et al, 2015;Özkök, 2010;Sünbül et al, 2002;Şengül Bircan, 2013;Ullah et al, 2015;) supports the result of this study. Another result of the study is that it was found that the mean of final attitude scores of the experimental group students towards the course did not show a statistically significant difference from the final attitude scores of the control group students in the teaching software prepared according to the teaching activities model by Gagne, but the arithmetic mean was higher.…”
Section: Discussionsupporting
confidence: 80%
“…The Gagne’s instructional model is a systematic approach to learning and its usefulness has been advocated in medical and nursing education. 2 , 22 Using the Gagne’s nine events of instruction, it caters to the different learning styles of learners and facilitates the learning processes of learners. To maximize its usefulness, the lesson plan can be contextualized to the other topics of phlebotomy like venipuncture and capillary puncture.…”
Section: Discussionmentioning
confidence: 99%